2020
DOI: 10.1177/1077801220940390
|View full text |Cite
|
Sign up to set email alerts
|

Two Studies Investigating Associations Between Sexual Assault Victimization History and Bystander Appraisals of Risk

Abstract: Across two studies, we examined sexual assault history and bystander appraisals of risk and the moderating roles of danger cue salience (Study 1) and alcohol intoxication (Study 2) in women. Participants (Study 1 = 148, Study 2 = 64) read vignettes ending with cues of nonconsensual sexual activity and an opportunity to intervene. Participants also completed self-report measures of vignette appraisals and history of sexual assault victimization. Across both studies, sexual assault victimization was unassociated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Overall, more severe SAV histories predicted increased bystander behaviors for women, disregarding their alcohol consumption; this may occur for several reasons. First, preliminary literature suggests that risk deficits brought on by SAV for an individual may not be evident when women are active bystanders (Bridges et al, 2020). In other words, women may have decreased abilities to recognize risk for themselves but not for others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, more severe SAV histories predicted increased bystander behaviors for women, disregarding their alcohol consumption; this may occur for several reasons. First, preliminary literature suggests that risk deficits brought on by SAV for an individual may not be evident when women are active bystanders (Bridges et al, 2020). In other words, women may have decreased abilities to recognize risk for themselves but not for others.…”
Section: Discussionmentioning
confidence: 99%
“…One relatively unexplored factor related to prosocial bystander behavior is sexual assault victimization (SAV) experiences, which can have a unique influence on risk recognition-a key component of bystander intervention (e.g., Bridges et al, 2020;Ham et al, 2019). For instance, some researchers have found that having an SAV experience can decrease risk recognition (Gidycz et al, 2006;Neilson et al, 2018;Rinehart & Yeater, 2015;Wilson et al, 1999), increase risk recognition (Gidycz et al, 2006;Untied et al, 2012) or have no effect on it (Gidycz et al, 2006;Yeater et al, 2009).…”
Section: Sexual Assault Victimizationmentioning
confidence: 99%
See 3 more Smart Citations